Barne-muinetako Sabin Arana Goiri. Gutunak I. (1876-1903): Prest. Joseba AgirreazKuenaga. Utriusque Vasconiae - Sudupe, Pako (EGAN, 2021)
PAKO SUDUPE. Barne-muinetako Sabin Arana Goiri. Gutunak I. (1876-1903) Prest. Joseba AgirreazKuenaga. Utriusque Vasconiae